Synthesis and Spectroscopic Investigation of Schiff Base Complexes of Lanthanides(III) - Rajewar, V.R.; Dharmale, M.K.; Pingalkar, S.R. (Asian Journal of Chemistry, 2015)
A series of La(III), Pr(III), Nd(III), Sm(III) and Tb(III) complexes have been synthesized with Schiff base (SAZ) derived from the condensation of salicylaldehyde with hydrazine. The prepared Schiff base and its lanthanide complexes have been characterized by elemental analysis, molar conductance,magnetic susceptibilities,UV-visible, IR, 1H NMR, thermal studies and XRD. The complexes have stoichiometry of the type [Ln(SAZ)2·2(H2O)]Cl3, for Pr(III), Sm(III) and Tb(III) where as [Ln(SAZ)2Cl2]Cl for La(III) and Nd(III), where the ligand SAZ coordinates to the lanthanide ion through azomethine nitrogen and phenolic oxygen of azine moiety.